PENINGKATAN PENGGUNAAN E-MONEY DI MASA PANDEMI COVID-19 - Ainiyah, Ghonimah Zumroatun; Aziz, Muhamad Nur; Permatasari, Kartika Dewi; Yubiharto, Yubiharto (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2023)
ABSTRACT The use of e-money is currently increasing along with the increasing use of the internet as a transaction tool. This shows that e-money has been accepted and used by the Indonesian people, besides the Covid-19 pandemic has also been a driving factor for the increasing use of e-money. This study aims to determine the effect of price discounts, ease of use, risk and promotion on interest in using e-money. This study uses quantitative methods, with primary data through questionnaires distributed to five universities in Banjarnegara with a population of 1,145 people. While the sample used is 92 respondents. Data analysis used instrument test (validity test and reliability test), classical assumption test (normality test, heteroscedasticity test and multicoloniarity test), multiple linear regression analysis and hypothesis testing using t test, F test and coefficient of determination. The data analysis tool uses SPSS. The results of the partial test showed that price discounts had a significant positive effect on interest in using e-money, ease of use had a significant positive effect on interest in using e-money, risk had no and no significant effect on interest in using e-money, promotion had a significant positive effect on interest using e-money. Simultaneous test results show that price discounts, ease of use, risk and promotions have a simultaneous effect on interest in using e-money. Because the public, especially students, will be more interested in using e-money when they get an advantage, including discounts, ease of use, low risk and promotions they receive. The value of the coefficient of determination is 0.592. This shows the ability of the independent variable in explaining the dependent variable is 59.2%, while the remaining 40.8% is influenced by other variables not examined in this study.